2015
DOI: 10.1007/s11746-015-2758-5
|View full text |Cite
|
Sign up to set email alerts
|

The Sterol and Erythrodiol + Uvaol Content of Virgin Olive Oils Produced in Five Olive‐Growing Zones of Extremadura (Spain)

Abstract: IntroductionToday, olives are grown in all the countries of the Mediterranean basin, especially in central and southern Spain, Italy, Greece, Turkey, Tunisia and Morocco. The world's total area of olive groves is around 10 million ha [1], of which approximately 98 % is in this Mediterranean region, with Spain standing out for its 24.4 % of the global total. Olives are the most important crop in Extremadura in terms of acreage, with some 269,350 ha, of which 70 % are in the province of Badajoz and 30 % in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…A similar case was observed in campesterol, where a total of 21.7% of the examined samples exceeded the legal maximum of 4%, with a mean value of 3.71% and ranged from 2.78 to 4.70%. A trend of higher campesterol has also been reported for cv Koroneiki, as well as for other cultivars cultivated in different countries [44,45], whereas the total sterol concentration of the most studied Spanish and Italian cultivars is always within the minimum limit of 1000 mg/kg [46][47][48][49][50].…”
Section: Analysis Of Sterolic Profile and Triterpenic Dialcohol Contementioning
confidence: 82%
“…A similar case was observed in campesterol, where a total of 21.7% of the examined samples exceeded the legal maximum of 4%, with a mean value of 3.71% and ranged from 2.78 to 4.70%. A trend of higher campesterol has also been reported for cv Koroneiki, as well as for other cultivars cultivated in different countries [44,45], whereas the total sterol concentration of the most studied Spanish and Italian cultivars is always within the minimum limit of 1000 mg/kg [46][47][48][49][50].…”
Section: Analysis Of Sterolic Profile and Triterpenic Dialcohol Contementioning
confidence: 82%
“…Arbequina agree with previous studies at different geographical locations that have suggested that environmental factors influence total sterols. [23][24][25]47,48 For example, total sterols were more than 2000 mg kg −1 oil at a warm location in California (USA), while they did not exceed 1800 mg kg −1 oil at cooler locations. 48 Moderate temperature increases under controlled, experimental conditions have also been shown to increase total sterols in soybean seeds, as reviewed by Carrera and Seguin.…”
Section: Discussionmentioning
confidence: 99%
“…30 Analysis of olive oils from five different growing regions in Extremadura, Spain, showed differences in total sterol and composition. 23 In Tunisian oils, differences were observed between regions in total and some individual sterols, particularly in ⊎-sitosterol, stigmasterol, and Δ7-stigmastenol. 24 Lower levels of campesterol in Tunisian oils were also observed in comparison with Portuguese or Spanish oils, although this may have been related to genotypic or environmental differences.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, 100% of the new samples used in the validation were classified correctly. This general validation strategy has been commonly used [21][22][23]. Linear regression was carried out to understand any relation between all analyzed parameters and irrigation treatment.…”
Section: Discussionmentioning
confidence: 99%